Literature review: The difficult management of face trauma (Research, Society and Development, 2023)
Face trauma today is directly linked to the use of alcohol, drugs, dangerous driving and the growing increase in urban violence, which are part of the world's reality. This study aims to highlight the importance of the clinician knowing the pathological processes that involve facial trauma, as well as its complications. In this way, the mutation suffered by the causes of facial trauma followed the modernity and severity of the temporal distribution and should be considered a priority in the study of treatment and prevention of these injuries. This study stands out as a descriptive qualitative study, called an integrative literature review, as it is a relevant instrument in the communication of research results, facilitating the use of these results in data analysis, as it provides a synthesis of the knowledge already produced and provides contributions to the improvement in the search for understanding of historical phenomena. Face trauma today is directly linked to the use of alcohol, drugs, dangerous driving and the growing increase in urban violence, which are part of the world's reality. In this way, the mutation suffered by the causes of facial trauma followed the modernity and severity of the temporal distribution and should be considered a priority in the study of treatment and prevention of these injuries. Therefore, after this analysis of the published works, it is evident the importance of carrying out public health policies aimed at controlling and preventing the occurrence of traumatisms, which can be directed towards peace in traffic, and the control of urban violence, as well as control of consumption. of alcoholic beverages and drugs among the young adult population.